2013
DOI: 10.1007/s00213-013-3282-7
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of anticipatory nausea in a rat model of contextually elicited conditioned gaping by enhancement of the endocannabinoid system

Abstract: JZL195 reduces AN primarily by acting as a FAAH inhibitor, but MAGL inhibition is also indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…From a clinical perspective, the present findings may become especially meaningful if FAAH inhibitors and/or metabolically stable forms of anandamide can provide medicinal (e.g., antinauseant, antiemetic, or appetite stimulant) effects in humans that have been reported in other species (e.g., Williams and Kirkham, 1999;Cross-Mellor et al, 2007;Rock et al, 2008;Parker et al, 2009;Limebeer et al, 2014;Sharkey et al, 2014). In that case, the present data support the view that the activation of CB 1 receptors by endocannabinoidsand in particular anandamide-may provide a therapeutic avenue with fewer deleterious effects on cognitive performance than produced by D 9 -THC.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…From a clinical perspective, the present findings may become especially meaningful if FAAH inhibitors and/or metabolically stable forms of anandamide can provide medicinal (e.g., antinauseant, antiemetic, or appetite stimulant) effects in humans that have been reported in other species (e.g., Williams and Kirkham, 1999;Cross-Mellor et al, 2007;Rock et al, 2008;Parker et al, 2009;Limebeer et al, 2014;Sharkey et al, 2014). In that case, the present data support the view that the activation of CB 1 receptors by endocannabinoidsand in particular anandamide-may provide a therapeutic avenue with fewer deleterious effects on cognitive performance than produced by D 9 -THC.…”
mentioning
confidence: 87%
“…One recent approach that has yielded encouraging preclinical results does not target the development of novel CB 1 agonists but instead involves enhancing endogenous cannabinergic activity by pharmacologically inhibiting the rapid metabolism of anandamide by fatty acid amide hydrolase (FAAH) (e.g., Kathuria et al, 2003;Seierstad and Breitenbucher, 2008;Gaetani et al, 2009;Pertwee, 2014). An emerging literature in which this approach is explored provides some preclinical evidence of efficacy in animal models of nausea, vomiting, and appetite (e.g., Williams and Kirkham, 1999;Cross-Mellor et al, 2007;Rock et al, 2008;Parker et al, 2009;Limebeer et al, 2014). However, the effects of anandamide on cognitive function in nonhuman primates have not yet been fully delineated, and consequently it is unclear whether anandamide (or other endocannabinoids) offer a therapeutic advantage over CB 1 agonists such as D 9 -THC.…”
mentioning
confidence: 99%
“…Most recently, it has been shown that rats also display conditioned gaping reactions when re-exposed to a contextual cues previously paired with a nauseating treatment, such as LiCl; thus, contextually elicited gaping in rats is analogous to contextually elicited nausea experienced by chemotherapy patients (Limebeer et al 2008; Rock et al 2008). Interestingly, just as in human chemotherapy patients, when contextually elicited conditioned gaping is produced it is not treatable with standard 5-HT 3 antiemetics (Limebeer et al 2006; Rock et al 2015), whereas cannabinoid compounds effectively reduce this behavior (Limebeer et al 2014; Rock et al 2008), likely by reducing the underlying nausea.…”
mentioning
confidence: 99%
“…We have previously demonstrated that systemic administration of the FAAH inhibitor, URB597 (0.3 mg/kg, but not 0.1 mg/kg), suppresses acute nausea (Cross-Mellor et al 2007) and anticipatory nausea (Rock et al 2008). Furthermore, the dual FAAH/MAGL inhibitor, JZL195 (10 mg/kg), also suppresses anticipatory nausea, primarily by elevating AEA in rat tissue (Limebeer et al 2014). Finally, we have shown that systemic administration of the MAGL inhibitor, MJN110 (10–20 mg/kg) suppresses acute and anticipatory nausea in rats by a CB 1 receptor-dependent action (Parker et al 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation